Assessing the effectiveness of advanced platelet rich fibrin in treating gingival recession: a systematic review and meta-analysis - Wafaa Saleh; Marwa Abdelhaleem; Samah Elmeadawy (BMC, 2024)
Abstract Objectives The literature lacks comprehensive evidence on the efficacy of advanced platelet rich fibrin(A-PRF) in treating gingival recession. Therefore, this systematic review and meta-analysis aimed to evaluate the effectiveness of A-PRF in the treatment of gingival recession. Materials and methods We adhered to the guidelines of PRISMA in searching the following databases: PubMed/MEDLINE, Embase, Cochrane Library, Web of Science, and Scopus to include all the eligible studies according to the prespecified inclusion and exclusion criteria. We conducted our search up to February 28, 2024. We conducted a meta-analysis of the primary and secondary clinical outcomes to measure the changes from baseline to 6 months after surgery. Results Our review included 10 randomized clinical trials in which 146 participants with 457 recession defects were included. We found that combination of A-PRF with various surgical techniques, such as coronally advanced flap (CAF) connective tissue graft (CTG), VISTA, tunneling, and pinhole surgical technique, demonstrated promising outcomes but varied by comparison group. We observed that CTG with CAF showed a higher reduction in recession depth in comparison to A-PRF with CAF. This review indicated no statistical or clinical differences in recession width, width of keratinized gingiva, probing depth, and clinical attachment level between the study and control groups. Conclusions Due to the less invasive nature of A-PRF, it provides a better clinical option to improve the outcomes of treating gingival recession. However, more well-designed RCTs with standardized approaches are needed to confirm these results.